Innovative policy interventions for transformation of farm sector - Ramesh Chand, (Agricultural Economics Research Review, 2023)
I feel privileged to deliver the presidential address in the 26th annual conference of Agricultural Economics Research Association (India). I thank the office bearers and members of the Association for giving me this honour.I am deviating from the standard practice of delivering a theme-based address built on sophisticated analysis or quantitative rigour and terminology of economics, and, presenting before you some simple propositions to bring long awaited and much needed changes in farm sector.